163k views
5 votes
(a+7) (a-7) how to check this problem


User Heehaaw
by
5.7k points

2 Answers

1 vote

Answer:

a² - 49

Explanation:

(a + 7)(a - 7) = ?

This is what we call us the difference of two squares.

Initially, a² - b² is written as (a + b)(a - b)

So the solution to (a + 7)(a - 7) is a² - 7²

That gives a² - 49

User Pableiros
by
5.1k points
0 votes

Answer:

(a + 7)(a - 7) = a² - 49

Explanation:

Use (a + b)(a - b) = a² - b²:

(a + 7)(a - 7) = a² - 7² = a² - 49

Other method:

Use FOIL: (a + b)(c + d) = ac + ad + bc + bd:

(a + 7)(a - 7) = (a)(a) + (a)(-7) + (7)(a) + (7)(-7) = a² - 7a + 7a - 49 = a² - 49

User Akinobu
by
4.8k points